Analysis of Spatial Patterns Based on Land Use in Stabat District, Langkat Regency, North Sumatra - Afiati Zata Dini; Charles Faucould Nahampun; Dafa Rizky Prayoga; Darwin Parlaungan Lubis; M Taufik Rahmadi; Sendi Permana (Universitas Pendidikan Indonesia, 2023)
The increase in human activity and development causes changes in land use, especially in urban areas such as Stabat District, the largest sub-district area as well as the densest population in Langkat Regency; of course, it cannot avoid the phenomenon, so this study aims to analyze the spatial pattern of the Stabat District area which is reviewed based on land use changes. Through digitization. This study uses a mixed approach with a sequential/staged method that combines or expands from quantitative methods at an early stage with qualitative descriptive method findings at a later stage. The results found are that almost all of the Stabat sub-districts are plantation areas because they are crossed by the main river and many tributaries, which are one of the factors on the periphery of plantation and agricultural land. There have been several changes in land use for five consecutive years from 2017-2021. Make that land use in Stabat District is dominated by land use as an open area or RTHK (City-scale Green Open Space), and the regional pattern of Stabat District uses a linear or elongated village pattern. This can be seen from the arrangement of residential areas and public facilities scattered on the main highway in Stabat District, which is also a Sumatran crossing connecting Aceh Province with North Sumatra Province.